Evaluation of the ambrosia beetles traps on Pterocarpus indicus in Indonesia - HAGUS TARNO; Yogo Setiawan; BAMBANG TRI RAHARDJO; JIANGUO WANG (Society for Indonesian Biodiversity, 2021)
Abstract. Tarno H, Setiawan Y, Rahardjo BT, Wang J. 2021. Evaluation of the  ambrosia beetles traps on Pterocarpus indicus in Indonesia. Biodiversitas 22: 1332-1339. Angsana, Pterocarpus indicus Willd., is a native tree of Southeast Asia. This tree is commonly planted in large numbers as an ornamental or shade plant along the roads, in parks, and in residential areas in Malang and Batu Cities of Indonesia. Ambrosia beetles Euplatypus parallelus (F.) and Treptoplatypus micrurus (Schedl.) have been reported to attack P. indicus trees in Malang and Batu Cities. Therefore, effective traps are required for early detection and monitoring of the spread of ambrosia beetles. This research aimed to evaluate the effectiveness of different traps and to investigate the diversity of ambrosia beetles on P. indicus trees in Malang and Batu Cities. This research was conducted along the roads in Malang and Batu Cities using four types of traps: funnel trap, window flight trap, bottle trap, and yellow sticky trap. Eleven ambrosia beetle species were collected in this research. The most abundant species were E. parallelus and Cryphalus laticollis (Browne). The funnel trap was the most effective for capturing ambrosia beetles, whereas the bottle trap was the least effective trap. The funnel trap captured more E. parallelus and C. laticollis individuals than other traps. The ambrosia beetles captured using different traps were categorized as having low diversity. The ambrosia beetles collected from Malang and Batu Cities were categorized as having moderate diversity.